Human Rights Implications of the Digital Revolution in Health Care in India - Deekshitha Ganesan (Harvard FXB Center for Health and Human Rights, 2022)
The COVID-19 pandemic has ushered in rapidly evolving developments in digital health, and governments around the world are experimenting with different ways of introducing technological tools in the management and delivery of health care services. India, among the countries that faced one of the most serious outbreaks in the second wave of the pandemic, recently rolled out the National Digital Health Mission, which promises an integrated but federated digital architecture and a digital health ecosystem that will solve the information asymmetries of the health care sector in India. While the promises of the National Digital Health Mission are many, India's experience with using another digital tool during the pandemic-the CoWIN portal for vaccine management-alerts us to the human rights concerns of rapid introductions of digital tools to address infrastructural and governance challenges in health care. This paper attempts to take a closer look at these two digital tools and the potential human rights implications of the National Digital Health Mission, particularly for the right to health.